Of Taps and Toilets : Evaluating Community Demand-Driven Projects in Rural India - World Bank (Washington, DC, 2017)
The study is conducted in two states with different geographic, public health, and socioeconomic characteristics, together spanning a range of conditions in rural India: Maharashtra and Orissa. The secondary objectives of the study were to develop proxy indicators for routine monitoring of the health impact of water and sanitation projects. A proxy is an easy-to-measure indicator for a hard to- measure impact. Here the goal is to identify the intermediate outcomes (for example coverage of toilets and taps) that are causally linked to the policy or intervention and to the outcome. The success of the analysis in establishing such links will determine the salience of the proxy indicators. Finally, World Bank also evaluate the broader impacts of water, sanitation, and hygiene interventions on rural livelihoods, such as savings in time, materials, and money invested in coping activities; improvements in convenience and privacy; and indirect benefits to caregivers (for example gains in work efficiency, and time and work reallocation within the household).